Membumikan Etika Sosial dan Pemahaman Multikultural Umat Beragama Melalui Pendidikan Tinggi - Andit Triono (Holistik, 2022)
ABSTRACTWhen looking at social interactions between communities, we cannot deny the presence of the influence of religious frames as the basis for people's thinking and acting. It is not uncommon for clashes between communities on the pretext of differences in religion and religious understanding that lead to multi-faceted conflicts as a result of globalization and "migrant labor" in which everyone starts looking for a living overseas, which is sometimes different from SARA. One of the obstacles that arises and becomes the source of conflict in a pluralistic society is the low understanding of multiculturalism which results in an unfamiliarity and an ineffectiveness in thinking and acting, which ultimately reduces social ethics which are actually the nature of God. This paper is a literature study that focuses on the fields of ethics and multiculturalism in the world of higher education which must be well aware of both its theory and application. Therefore, this paper critically examines the concept of ethics education and multiculturalism for students as potential future figures so that they are able to apply well in public spaces, social media, and families when they are or have been in college.